Some exact solutions of the Boltzmann equation - Skakauskas, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Скакаускас. Некоторые точные решения уравнения БольцманаV. Skakauskas. Kai kurie tikslūs Bocmano lygties sprendiniai